GALICIAN SPACE IN THE PRAGUE SPACE. CZECH ESSAYS BY HONORATA Z WIŚNIOWSKICH ZAPOVÁ ABOUT HUTSULS AND RUTHENIANS FROM THE AREA OF THE RIVER PRUT - Tarajło-Lipowska, Zofia (Porównania, 2013)
Honorata z Wiśniowskich Zapová (1825–1856) was a Polish noblewoman from western Ukraine whose marriage with the Czech official Karl Vladislav Zap brought her to Prague. She published texts in Czech in which she described the space of her childhood. She gave them the character of ethnographic essays presenting Galicia and Ukraine, lands inhabited by Slavic brothers very much different from the Czechs. These works emanate with a longing for the lost land, its idealization and evaluating it higher than the Prague space which she infiltrated. The Prague space disappointed her but the writer aimed at enrich it not only by her own memories but also through her continuous work in the realms of literature, pedagogy and society.